Recent advances in dual- and multi-responsive nanomedicines for precision cancer therapy - Zhang, Yijing (2023)
Nanomedicines have been regarded as a potential approach in the field of cancer treatment due to their unique advantages. Although improved therapeutic efficacy can be achieved, the applications of most traditional nanomedicines are still limited by severe side effects resulting from unintended retention of therapeutic agents in non-diseased tissues. To increase the controllability of therapeutic agent accumulation in targeting sites (such as tumors), stimuli-responsive nanomedicines that realize drug release in response to exogenous or endogenous stimuli have been developed. In these stimuli-responsive nanomedicines, most of them are activated by mono type of stimulus, and therefore show unsatisfactory selectivity and specificity. In contrast, dual- and multi-responsive nanomedicines that integrate different responsive components into a signal nanoplatform can allow drug release in a more safe and effective manner, leading to both improved therapeutic efficacy and reduced systemic toxicity. Herein, we summarize recent advances in precision cancer therapy by using dual- and multi-responsive nanomedicines. The design strategies and working mechanisms of these dual- and multi-responsive nanomedicines and their applications in chemotherapy, phototherapy, and immunotherapy of cancer are introduced in detail. The existing challenges and future prospects are finally discussed in anticipation of accelerating the clinical translation of these nanomedicines.